Burns in Dorset: Goadly's Weekly Entertainer and Early Magazine Treatment of Burns, 1793–1821. Issue 1 (March 2021) - Scott, Patrick
Abstract : Discusses thirty-one items by or about Robert Burns, none previously noted in Burns scholarship, which were reprinted in a Sherborne, Dorset, weekly magazine, a few in Burns's life-time, most, and more frequently, after his death in 1796, and suggests that the usual focus in Burns reception study on first book publication and the early reviews needs to be complemented by awareness of the dissemination of Burns material through such widespread reprinting in magazines, as also in newspapers, chapbooks, and anthologies.